A method for modifying a rockified bearing stratum foundation
Patent Information
- Application Number
- CN202611064950.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-17
- Publication Date
- 2026-10-23
AI Technical Summary
[0006]然而,原位地基土体通常具有含水状态、颗粒组成、孔隙结构和可溶性组分分布不均等特点,固化材料在现场搅拌和固化过程中受到土体差异及液相变化影响,容易导致不同部位的固化反应程度存在差异
(1)本发明以粒化高炉矿渣粉、硅酸盐熟料、粉煤灰、无水石膏及碱性活性激发剂形成基础反应体系,使基础固化浆料进入原位土体后形成胶凝反应条件。在此基础上,并非仅依据原位土体表面泌水现象判断施工异常,而是沿处理深度方向取得液相样品,以施工前对应位置的本底钠离子浓度和本底可溶性硅浓度作为校正基础,分别确定现场钠离子增量和现场可溶性硅增量。由此,可以降低不同施工单元原位含盐背景和土体离子差异对判断结果的影响,并将固化过程中因液相迁移造成的激发组分上部富集和下部亏损状态从一般泌水现象中区分出来,为后续针对性处理提供更明确的施工依据。
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of foundation treatment, and in particular to a method for treating foundations modified with lithified bearing strata. Background Technology
[0002] Foundation treatment is an important technical means to improve the bearing capacity, deformation stability, and engineering applicability of deep, soft soil layers. In roads, industrial floors, storage yards, and other load-bearing foundation projects, in-situ solidification treatment is widely used because it reduces the amount of earthwork required for replacement, lowers the need for off-site disposal, and improves construction efficiency. This type of treatment typically involves adding cement, mineral admixtures, activating components, or solidifying materials to the in-situ soil, followed by mixing, compaction, and curing, to form a solidified layer with a certain bearing capacity.
[0003] Existing technologies include methods for treating weak foundations using mineral cementing materials or alkali-activated cementing materials. For example, CN105541138B discloses a geopolymer for treating saline soil foundations, its preparation method, and its application. This geopolymer is formed from blast furnace slag, fly ash, zeolite powder, and an alkaline activator, and is applied to the reinforcement of saline soil foundations. This type of technology utilizes active mineral materials and activating components to form a cementitious structure, thereby improving the mechanical properties and durability of the treated soil.
[0004] Regarding construction techniques, existing technologies have also proposed staged admixture and repeated mixing methods for specific soft soil types. For example, CN101349060B discloses a cement and fly ash secondary mixing and spraying method for reinforcing organic soft soil. This method targets soft soil with high natural water content and organic matter content, using fly ash and cement as admixtures, and improving the strength of the mixture through secondary mixing. This type of construction method demonstrates that using solidification materials combined with repeated mixing for in-situ soft soil layers is an existing technical approach to improving foundation treatment effects.
[0005] Furthermore, the evaluation of the construction quality of the solidification treatment layer has also attracted attention. For example, CN102980919B discloses a method for determining the uniformity of cement-mixed soil by combining pH value and electrical conductivity testing. This method determines the critical detection parameters through on-site indoor soil mix proportion tests and tests the pH value and electrical conductivity of the cement-mixed soil to be tested, thereby evaluating the uniformity and average strength of the cement-mixed soil. This type of method provides a quantitative evaluation approach for the construction quality testing of solidified soil.
[0006] However, in-situ foundation soils typically exhibit characteristics such as uneven water content, particle composition, pore structure, and distribution of soluble components. During on-site mixing and curing, the curing material is affected by soil variations and liquid phase changes, easily leading to differences in the degree of curing reaction at different locations. Even with the use of curing materials, repeated mixing during construction, or post-construction testing and evaluation, it remains difficult to consistently guarantee the uniformity of the cured layer within the treatment depth range, thus affecting the consistency and long-term stability of the foundation's bearing capacity.
[0007] Therefore, how to improve the curing uniformity of the load-bearing layer formed by in-situ curing within the treatment depth range is a technical problem that still needs to be solved in this field. Summary of the Invention
[0008] The purpose of this invention is to overcome the above-mentioned problems in the prior art and provide a method for modifying the foundation with a lithified basement, so as to improve the solidification uniformity of the basement formed by in-situ solidification treatment within the treatment depth range, and improve the consistency and long-term stability of the foundation bearing capacity.
[0009] To achieve the above objectives, the present invention provides a method for treating a modified foundation of a lithified basement, comprising the following steps: S1: Divide the in-situ foundation to be treated into multiple unit construction units, each unit construction unit having the same area and treatment depth, denoted as H; set no less than three sampling positions along the treatment depth direction within each unit construction unit, and obtain soil samples before construction from each sampling position, prepare soil sample leachates under the same leachate conditions, and determine the background sodium ion concentration and background soluble silica concentration in each soil sample leachate; mix and homogenize each of the soil samples before construction according to the same dry soil mass fraction to obtain a reference soil sample, and determine the reference background sodium ion concentration and reference background soluble silica concentration in the reference soil sample leachate; S2: Mix the basic reactive dry material with water according to the water-cement ratio to obtain the basic curing slurry; mix the basic curing slurry with the reference soil sample according to the same dry soil content of the basic reactive dry material to obtain the reference initial mixed body; and inject the basic curing slurry into the in-situ soil of each of the above-mentioned construction units for in-situ mixing to obtain the on-site initial mixed slurry-soil mixture of each of the above-mentioned construction units. S3: At the stage where the initial mixed slurry mixture on site shows bleeding but has not yet reached initial setting, a reference wet sample is obtained from the reference initial mixed slurry mixture, and on-site wet samples are obtained from each of the sampling locations of each of the unit construction units; under the same pressure filtration conditions, solid-liquid separation is performed on the reference wet sample and each of the on-site wet samples to obtain a reference liquid phase sample and an on-site liquid phase sample corresponding to each of the sampling locations; the sodium ion concentration and soluble silicon concentration in the reference liquid phase sample and each of the on-site liquid phase samples are determined respectively. S4: The difference between the sodium ion concentration in the reference liquid sample and the reference background sodium ion concentration is determined as the reference sodium ion increment; the difference between the soluble silicon concentration in the reference liquid sample and the reference background soluble silicon concentration is determined as the reference soluble silicon increment; the difference between the sodium ion concentration in each of the field liquid samples and the background sodium ion concentration at the corresponding sampling location is determined as the field sodium ion increment; the difference between the soluble silicon concentration in each of the field liquid samples and the background soluble silicon concentration at the corresponding sampling location is determined as the field soluble silicon increment. When the in-situ sodium ion increment and in-situ soluble silica increment corresponding to at least one sampling position located above the treatment depth in a unit construction unit are both higher than the corresponding reference sodium ion increment and reference soluble silica increment, and the in-situ sodium ion increment and in-situ soluble silica increment corresponding to at least one sampling position located below the sampling position are both lower than the corresponding reference sodium ion increment and reference soluble silica increment, the unit construction unit is determined as a migration replenishment construction unit; the continuous depth segment where the in-situ sodium ion increment and in-situ soluble silica increment are both higher than the corresponding reference increment is determined as a migration enrichment segment, and the continuous depth segment located below the migration enrichment segment where the in-situ sodium ion increment and in-situ soluble silica increment are both lower than the corresponding reference increment is determined as a migration deficit segment; S5: Collect the oozing liquid that precipitates from the initial mixed slurry before it reaches initial setting in the migration and replenishment construction unit. Use the oozing liquid as the only mixing liquid and mix it with the replenishment reaction dry material to obtain the migration liquid replenishment slurry. The replenishment reaction dry material does not contain sodium carbonate, sodium metasilicate, sodium hydroxide, or potassium hydroxide. S6: Inject the migration fluid replenishment slurry into the migration deficit section, and perform local in-situ re-stirring in the migration deficit section. Then, perform penetrating in-situ re-stirring along the direction from the migration deficit section to the migration enrichment section, so that the migration fluid replenishment slurry is dispersed within the treatment depth range of the migration replenishment construction unit. S7: After completing the in-situ re-mixing and before the initial setting of the on-site mixed slurry, obtain compensated wet samples from the migration enrichment section and the migration deficit section respectively. Under the same pressure filtration and detection conditions as in step S3, measure the compensated sodium ion increment and the compensated soluble silica increment. When the difference in the compensated sodium ion increment between the migration enrichment section and the migration deficit section is less than the difference in the on-site sodium ion increment before re-mixing, and the difference in the compensated soluble silica increment is less than the difference in the on-site soluble silica increment before re-mixing, stop injecting migration liquid to the migration deficit section to replenish the slurry. S8: Level, compact and moisturize the in-situ foundation after in-situ mixing treatment to form a modified foundation with lithified matrix bearing layer; The basic reaction dry materials include granulated blast furnace slag powder, silicate clinker, fly ash, anhydrous gypsum and alkaline active activator, wherein the alkaline active activator includes sodium carbonate and anhydrous sodium metasilicate. The water-cement ratio is the ratio of the mass of water in the base curing slurry to the mass of the base reactive dry material.
[0010] Preferably, in step S1, three sampling positions are set along the treatment depth direction within each unit construction unit. The three sampling positions are respectively located within the depth range of 0.15H~0.25H, 0.45H~0.55H and 0.75H~0.85H from the surface of the original foundation. The soil sample before construction is formed by mixing soil samples obtained from at least two sampling points circumferentially distributed at the corresponding sampling positions.
[0011] Preferably, the same extraction conditions in step S1 include the same dry soil mass, the same water-to-soil mass ratio, the same shaking time, the same settling time, the same solid-liquid separation method, and the same detection temperature; The same pressure filtration conditions in step S3 include the same wet sample volume, the same pressure filtration pressure, the same pressure filtration time, and the same filter membrane pore size; The sodium ion concentration was determined by inductively coupled plasma atomic emission spectrometry, and the soluble silicon concentration was determined by molybdenum blue spectrophotometry.
[0012] Preferably, based on a total mass of 100 parts by mass of the basic reaction dry material, the basic reaction dry material consists of 48-54 parts by mass of granulated blast furnace slag powder, 20-24 parts by mass of silicate clinker, 14-18 parts by mass of fly ash, 7-9 parts by mass of anhydrous gypsum, and 5-7 parts by mass of alkaline active activator.
[0013] Preferably, the mass ratio of sodium carbonate to anhydrous sodium metasilicate in the alkaline active activator is 1:0.65-0.80; the mass of the basic reaction dry material accounts for 9%-13% of the mass of the dry soil in situ within the corresponding construction unit; and the water-cement ratio is 0.43-0.58.
[0014] Preferably, the replenishment reaction dry material includes granulated blast furnace slag powder, metakaolin, and anhydrous gypsum; based on a total mass of 100 parts by mass of the replenishment reaction dry material, the replenishment reaction dry material is composed of 62-72 parts by mass of granulated blast furnace slag powder, 20-30 parts by mass of metakaolin, and 6-10 parts by mass of anhydrous gypsum.
[0015] Preferably, the specific surface area of the granulated blast furnace slag powder in the basic reaction dry material is 400-480 m² / kg, the specific surface area of the granulated blast furnace slag powder in the replenishment reaction dry material is 560-680 m² / kg, and the particle size D50 of the metakaolin is 2-6 μm.
[0016] Preferably, in step S4, when the increase in the on-site sodium ion increment in the migration enrichment section relative to the reference sodium ion increment is not less than 12%, and the increase in the on-site soluble silicon increment in the migration enrichment section relative to the reference soluble silicon increment is not less than 10%, and the decrease in the on-site sodium ion increment in the migration deficit section relative to the reference sodium ion increment is not less than 8%, and the decrease in the on-site soluble silicon increment in the migration deficit section relative to the reference soluble silicon increment is not less than 8%, the corresponding unit construction unit is determined as the migration replenishment construction unit.
[0017] Preferably, in step S5, the mass ratio of the oozing liquid to the replenishment reaction dry material is 0.45:1 to 0.70:1; the mass of the replenishment reaction dry material added to one of the migration replenishment construction units is 4% to 10% of the mass of the basic reaction dry material already added in the migration replenishment construction unit.
[0018] Preferably, in step S7, when the difference in sodium ion increment after compensation between the migration enrichment section and the migration deficit section decreases by no less than 35% relative to the difference in sodium ion increment before re-stirring, and the difference in soluble silica increment after compensation between the migration enrichment section and the migration deficit section decreases by no less than 30% relative to the difference in soluble silica increment before re-stirring, the injection of migration liquid to replenish the slurry in the migration deficit section is stopped. When the difference in sodium ion increment or the difference in soluble silicon increment after compensation does not meet the aforementioned reduction ratio, steps S5 to S7 shall be repeated before the initial setting of the on-site mixed slurry reaches the initial setting stage; the cumulative mass of the replenished reactive dry material shall not exceed 12% of the mass of the basic reactive dry material already added in the migration replenishment construction unit.
[0019] The present invention, by adopting the above technical solution, has the following beneficial effects: (1) This invention uses granulated blast furnace slag powder, silicate clinker, fly ash, anhydrous gypsum, and alkaline active activator to form a basic reaction system, so that the basic solidification slurry enters the in-situ soil and forms the conditions for gelation reaction. On this basis, instead of judging construction anomalies solely based on the surface bleeding phenomenon of the in-situ soil, liquid phase samples are obtained along the treatment depth direction. The background sodium ion concentration and background soluble silica concentration at the corresponding location before construction are used as the correction basis to determine the on-site sodium ion increment and on-site soluble silica increment, respectively. Thus, the influence of the in-situ salinity background and soil ion differences between different construction units on the judgment results can be reduced, and the enrichment of the upper part and the depletion of the lower part of the activating component caused by liquid phase migration during the solidification process can be distinguished from general bleeding phenomena, providing a clearer construction basis for subsequent targeted treatment.
[0020] (2) After determining the migration enrichment section and the migration deficit section, this invention collects the oozing liquid precipitated by the migration replenishment construction unit before initial setting. This oozing liquid is used as the sole mixing liquid and mixed with a dry replenishment reaction material that does not contain sodium carbonate, sodium metasilicate, sodium hydroxide, or potassium hydroxide to form a migration liquid replenishment slurry. The migration liquid replenishment slurry is then directionally injected into the migration deficit section. This treatment method does not continue to add new soluble alkaline components to the abnormal area, but rather reintroduces the reaction components that have migrated with the liquid phase into the depth area where the deficit occurs. This transforms the migration liquid phase, which would originally cause uneven reaction distribution within the treatment layer, into an on-site mixing medium for the replenishment reaction. This helps to reduce the risk of secondary migration, local alkali accumulation, and surface salt precipitation caused by adding extra water and alkaline activators.
[0021] (3) In this invention, the migration fluid replenishment slurry is preferentially injected into the migration deficit section, and after local in-situ re-stirring in the migration deficit section, it is then carried out through in-situ re-stirring along the direction from the migration deficit section to the migration enrichment section. This treatment sequence is different from the treatment method of uniformly adding solidifying material to the entire treatment depth or adding liquid-absorbing powder only at the bleeding enrichment location. It can first compensate for the depth area where the reaction components are insufficient during the in-situ solidification process, and then redistribute the slurry-soil mixture that has been partially compensated within the treatment depth range through through re-stirring. This is beneficial to reduce the difference in solidification reaction between the upper enrichment area and the lower deficit area, and improve the uniformity and overall bearing stability of the formed lithified matrix bearing layer in the depth direction.
[0022] (4) After completing the backfilling and through-mixing, the present invention again measures the increased sodium ions and increased soluble silica after compensation in the migration enrichment and migration deficit sections, and uses the change in the difference in increments between the two depth sections as the basis for stopping the injection of migration liquid backfill slurry. This feedback control method makes the backfilling operation no longer dependent on the preset amount of material or construction experience, but corresponds to the actual improvement of the migration state of the activated components on site. This is beneficial to avoid insufficient backfilling causing the lower solidification reaction to remain weak, and also to avoid excessive backfilling leading to material waste or local reaction imbalance, thereby improving the controllability of the foundation treatment process and the consistency of the treatment results. Detailed Implementation The following provides a detailed description of specific embodiments of the present invention. It should be understood that the specific embodiments described herein are for illustrative and explanatory purposes only and are not intended to limit the scope of the invention.
[0023] Unless otherwise defined, all scientific and technical terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art.
[0024] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0025] Unless otherwise specified, all materials and reagents used in the following examples are commercially available.
[0026] The present invention will now be described in detail with reference to specific embodiments, which are intended to understand rather than limit the invention.
[0027] Example 1 This embodiment discloses a method for modifying the foundation of a lithified base bearing layer. Addressing the problem that migratable activating components in the foundation solidification slurry migrate along the treatment depth direction with the bleed liquid during in-situ foundation treatment, resulting in an enrichment of activating components in the upper part of the treated layer and a depletion of activating components in the lower part, the method determines the enriched and depleted migration sections by detecting the increase in sodium ions and soluble silica. The bleed liquid precipitated from the migration replenishment construction unit is collected, and this bleed liquid is used as the sole mixing liquid to prepare a migration replenishment slurry without added alkali. The migration replenishment slurry is then directionally injected into the depleted migration section and subjected to in-situ re-stirring.
[0028] The basic reaction dry material, based on a total mass of 100.00 parts by weight, consists of the components shown in Table 1.
[0029] Table 1 The replenishment reaction dry material, based on a total mass of 100.00 parts by weight, consists of the components shown in Table 2.
[0030] Table 2 The ultrafine granulated blast furnace slag powder is prepared as follows: 500 kg of granulated blast furnace slag powder is dried at 105℃ for 2 hours and then added to a ceramic-lined ball mill; alumina grinding balls with diameters of 20 mm, 10 mm, and 5 mm are added in a mass ratio of 3:4:3, with a total mass of 1000 kg; the ball mill speed is controlled at 32 r / min, and continuous grinding is performed for 180 min; the ground slag powder is then classified by an air classifier with a classifier wheel speed of 3200 r / min, resulting in a specific surface area of 620 m². 2 / kg of ultrafine blast furnace slag powder.
[0031] In this embodiment, three adjacent construction units are selected, numbered A1, A2, and A3 respectively. The mass of the in-situ dry soil in each construction unit is 40,000 kg, and the mass of the foundation reactive dry material accounts for 11.00% of the mass of the in-situ dry soil. 4,400 kg of foundation reactive dry material is added to each construction unit. The water-cement ratio of the foundation curing grout is 0.50, and 2,200 kg of grout mixing water is added to each construction unit.
[0032] The specific amount of basic reactive dry material used in each construction unit is shown in Table 3.
[0033] Table 3. Basic reactive dry matter usage for each construction unit. In this embodiment, A2 is identified as the migration replenishment construction unit where the activating component migration occurs. The mass of the replenishment reaction dry material added to A2 is 7.00% of the mass of the previously added basic reaction dry material, i.e., 308.00 kg. The specific amount of the replenishment reaction dry material is shown in Table 4.
[0034] Table 4. Replenishment of Dry Material Consumption for Construction Unit A2 In the migration fluid replenishment slurry, the mass ratio of the bleed fluid to the replenishment reaction dry material is 0.55:1. Therefore, the mass of the bleed fluid used to prepare the migration fluid replenishment slurry is 169.40 kg, and the total mass of the resulting migration fluid replenishment slurry is 477.40 kg.
[0035] The specific methods for modifying the foundation of the lithified basement are as follows.
[0036] S1. Division of construction units and in-situ soil testing before construction. The construction area was selected from a continuously distributed area of soft plastic silty clay within the industrial stockpile to be treated. The construction area is 12.00m long and 4.00m wide, with a total area of 48.00m². The construction area was divided into three construction units along its length: A1, A2, and A3. Each construction unit is 4.00m long and 4.00m wide, with an area of 16.00m². 2 The processing depth H is 2.00m.
[0037] Before construction, sampling and testing showed that the wet density of the in-situ soil in the three construction units was 1.775 g / cm³, the moisture content was 42.0%, and the dry soil mass of the in-situ soil within the treatment area of each construction unit was 40,000 kg.
[0038] Three sampling locations were set up along the treatment depth direction within each construction unit. The first sampling location was located in a continuous depth section of 0.30–0.50 m from the surface of the original foundation, with a center depth of 0.40 m; the second sampling location was located in a continuous depth section of 0.90–1.10 m from the surface of the original foundation, with a center depth of 1.00 m; and the third sampling location was located in a continuous depth section of 1.50–1.70 m from the surface of the original foundation, with a center depth of 1.60 m.
[0039] At each sampling location, soil samples were obtained using a thin-walled soil sampler at four circumferential locations 1.00m from the center point of the corresponding construction unit. 1000g of wet soil sample was obtained at each circumferential location. The four wet soil samples obtained at the same sampling location were mixed evenly to obtain the soil sample of that sampling location before construction.
[0040] Each soil sample before construction was dried in a 40℃ forced-air drying oven until constant weight. 100.00g of the dried soil sample was weighed and 500.00g of deionized water (with a conductivity of 4.5μS / cm at 25℃) was added. The soil sample and deionized water were placed in a polyethylene sealed bottle and shaken at 200r / min for 30min, then allowed to stand for 60min. The extract was then filtered through a 0.45μm polyethersulfone membrane to obtain the soil extract corresponding to each sampling location.
[0041] The background sodium ion concentration in the leachate of each soil sample before construction was determined by inductively coupled plasma atomic emission spectrometry, and the background soluble silica concentration in the leachate of each soil sample before construction was determined by silicomolybdenum blue spectrophotometry.
[0042] 2000.00g of dry soil samples were weighed from each of the three sampling locations A1, A2, and A3, totaling 18000.00g of pre-construction dry soil samples. These soil samples were then mixed and homogenized to obtain the reference soil sample. 100.00g of the reference soil sample was weighed, and a reference soil extract was prepared under the same extraction conditions as described above. The baseline sodium ion concentration was measured to be 43.0mg / L, and the baseline soluble silica concentration was measured to be 11.0mg / L.
[0043] The baseline test results of each sampling location in the A2 unit before construction are shown in Table 5.
[0044] Table 5. Baseline test results before construction of Unit A2 S2. Preparation of basic curing slurry and in-situ initial mixing treatment Weigh out the granulated blast furnace slag powder, silicate cement clinker, Grade I low-calcium fly ash, anhydrous calcium sulfate, sodium carbonate, and anhydrous sodium metasilicate according to the weight proportions shown in Table 1.
[0045] First, granulated blast furnace slag powder, silicate cement clinker, Grade I low-calcium fly ash and anhydrous calcium sulfate are added to a horizontal twin-shaft dry powder mixer and mixed for 5 minutes at a speed of 45 r / min. Then, sodium carbonate and anhydrous sodium metasilicate are added and mixed for another 3 minutes at a speed of 45 r / min to obtain the basic reaction dry material.
[0046] For each construction unit, weigh out 4400.00 kg of foundation reactive dry material and 2200.00 kg of deionized water. First, add 1760.00 kg of deionized water to the slurry mixing tank, start the paddle mixer and control the speed at 180 r / min; add 4400.00 kg of foundation reactive dry material at a uniform rate over 10 minutes; after the foundation reactive dry material has been added, continue to add the remaining 440.00 kg of deionized water, and stir for 6 minutes at a speed of 240 r / min to obtain the foundation curing slurry. The interval between the preparation of the obtained foundation curing slurry and its injection into the in-situ soil is controlled to be 12 minutes.
[0047] For the reference soil sample, weigh 18000.00g of reference soil sample, add 1980.00g of basic reaction dry material and 990.00g of deionized water, and stir for 5min at a speed of 120r / min to obtain the initial mixing mixture of the reference soil.
[0048] For the three construction units A1, A2, and A3, a tracked in-situ soil mixing device was used for treatment. The device is equipped with a twin-shaft mixing head, with a single mixing width of 2.00m. Each construction unit is divided into two mixing belts along the width direction, each mixing belt being 4.00m long, 2.00m wide, and 2.00m deep.
[0049] During construction, the twin-shaft mixing head cuts into the in-situ soil from the ground surface at a speed of 90 r / min, with a downward speed of 0.40 m / min. Simultaneously, foundation solidification grout is injected, with 3300.00 kg of grout injected into each mixing zone. After reaching a treatment depth of 2.00 m, the mixing head moves upward at a speed of 0.50 m / min to re-mix to the ground surface. After each construction unit completes the treatment of two mixing zones, a preliminary mixed grout-soil mixture is obtained on-site.
[0050] The time when each construction unit completes the injection of foundation solidification grout and the first upward re-mixing is taken as the initial mixing completion time of the corresponding construction unit. The initial setting time of the same batch of on-site initially mixed grout mixture was pre-measured and found to be 318 minutes.
[0051] S3. Acquisition of liquid phase samples after initial stirring and detection of excited component migration. Sixty minutes after the initial mixing of each construction unit was completed, a continuous film of oozing water was observed on the surface of the initially mixed slurry-soil mixture, at which point the initial setting state had not yet been reached.
[0052] Weigh 500.00g of reference wet sample from the initial mixed mixture. Obtain 500.00g of field wet sample from the first, second, and third sampling positions of the three construction units A1, A2, and A3.
[0053] All wet samples were collected vertically along the corresponding continuous depth section using a thin-walled sampling tube with an inner diameter of 50 mm. Immediately after sampling, the wet samples were placed in sealed polyethylene bags and transported to a mobile testing vehicle located next to the construction area for processing within 10 minutes.
[0054] The reference wet sample and the field wet sample were respectively placed into a pressure filtration device and solid-liquid separation was performed under the same conditions of filtration pressure of 0.30 MPa, filtration time of 5 min and filter membrane pore size of 0.45 μm to obtain the reference liquid phase sample and the field liquid phase sample respectively.
[0055] The sodium ion concentration in each liquid sample was determined using inductively coupled plasma atomic emission spectrometry (ICP-AES). A standard curve was established before testing using sodium ion standard solutions with concentrations of 0 mg / L, 50 mg / L, 100 mg / L, 250 mg / L, 500 mg / L, and 750 mg / L.
[0056] The concentration of soluble silicon in each liquid sample was determined using the silicomolybdenum blue spectrophotometric method. During the determination, the liquid sample was diluted 10-fold, and the absorbance was measured at a wavelength of 815 nm. The concentration of soluble silicon in the liquid sample was then calculated based on the soluble silicon standard curve.
[0057] The sodium ion concentration in the reference liquid sample was 523.0 mg / L, and the soluble silicon concentration was 131.0 mg / L. Therefore, the increase in sodium ion concentration was 480.0 mg / L, and the increase in soluble silicon concentration was 120.0 mg / L.
[0058] S4. Determination of relocation and replenishment construction units, relocation enrichment sections, and relocation deficit sections. The sodium ion concentration at each sampling location was subtracted from the sodium ion concentration at each sampling location to obtain the on-site sodium ion increment; the soluble silicon concentration at each sampling location was subtracted from the soluble silicon concentration at each sampling location to obtain the on-site soluble silicon increment.
[0059] The on-site sodium ion increase and on-site soluble silica increase for each construction unit are shown in Table 6.
[0060] Table 6. Detection results of the increase in activating components after initial mixing in each construction unit. For construction unit A2, the on-site sodium ion increment at the first sampling location was 576.0 mg / L, an increase of 20.0% compared to the baseline sodium ion increment of 480.0 mg / L; the on-site soluble silica increment was 148.0 mg / L, an increase of 23.3% compared to the baseline soluble silica increment of 120.0 mg / L.
[0061] The on-site sodium ion increment at the third sampling location of construction unit A2 was 420.0 mg / L, a decrease of 12.5% compared to the baseline sodium ion increment of 480.0 mg / L; the on-site soluble silica increment was 105.0 mg / L, a decrease of 12.5% compared to the baseline soluble silica increment of 120.0 mg / L.
[0062] Therefore, the A2 unit construction unit simultaneously meets the criteria that the increase in sodium ion concentration at the upper sampling location is not less than 12% and the increase in soluble silica concentration at the upper sampling location is not less than 10%, and the decrease in sodium ion concentration at the lower sampling location is not less than 8% and the decrease in soluble silica concentration at the lower sampling location is not less than 8%. Thus, the A2 unit construction unit is determined as a migration and replenishment construction unit.
[0063] The 0.30–0.50 m continuous depth section corresponding to the first sampling position in the A2 unit construction unit was identified as the migration enrichment section, and the 1.50–1.70 m continuous depth section corresponding to the third sampling position was identified as the migration deficit section.
[0064] Since neither construction unit A1 nor unit A3 simultaneously exhibited an increase in sodium ion and soluble silica in the upper part, nor a decrease in sodium ion and soluble silica in the lower part, no migration fluid replenishment slurry injection treatment was performed.
[0065] S5. Preparation of Migration Liquid Replenishment Slurry 112 minutes after the initial mixing of the A2 unit construction module, a polyethylene collection tank was used to collect the oozing liquid precipitated from the surface of the initially mixed slurry-soil mixture. The collection tank was arranged around the perimeter of the A2 unit construction module, with the bottom of the tank 20mm below the treated surface. During the collection process, a polyethylene scraper was used to introduce a continuous liquid film from the surface into the collection tank, and a peristaltic pump was used to transport the oozing liquid in the collection tank to a sealed polyethylene storage tank.
[0066] The collected effluent was filtered through a nylon filter with a pore size of 100 μm to remove larger soil particles. 169.40 kg of the filtered effluent was weighed for later use. Simultaneous sampling and analysis revealed that the sodium ion concentration in the effluent was 604.0 mg / L and the soluble silicon concentration was 153.0 mg / L.
[0067] Weigh out 206.36 kg of ultrafine blast furnace slag powder, 77.00 kg of metakaolin, and 24.64 kg of anhydrous calcium sulfate according to the dosages shown in Table 4. First, add the ultrafine blast furnace slag powder and metakaolin to a closed dry powder mixer and mix for 4 minutes at a speed of 50 r / min; then add anhydrous calcium sulfate and continue mixing for 3 minutes to obtain 308.00 kg of replenishment reaction dry material.
[0068] 169.40 kg of bleed liquid was added to a vertical pulping tank with a capacity of 800 L. The agitator was started and the speed was controlled at 160 r / min. 308.00 kg of replenishment reaction dry material was added evenly within 5 min. After the replenishment reaction dry material was added, the agitator speed was increased to 240 r / min and stirring was continued for 6 min to obtain 477.40 kg of migration liquid replenishment slurry.
[0069] During the preparation of the migration fluid replenishment slurry, no external water, sodium carbonate, anhydrous sodium metasilicate, sodium hydroxide, or potassium hydroxide are added.
[0070] S6. Directional injection of migration fluid replenishment slurry into the migration deficit section and in-situ re-mixing. The A2 unit construction cell is divided into two equal parts along both the length and width directions, forming four injection zones each measuring 2.00m × 2.00m. Each injection zone corresponds to 119.35kg of backfill grout injected with migration fluid.
[0071] A hollow grouting mixing rod with lateral grout outlets is used for directional injection. The outer diameter of the hollow grouting mixing rod is 60 mm, and the lateral grout outlets are located at positions 100 mm, 150 mm, and 200 mm from the end of the rod. During construction, the hollow grouting mixing rod is inserted to a depth of 1.65 m from the original foundation surface, so that the lateral grout outlets are located within the migration loss section of 1.50–1.70 m.
[0072] Within each injection zone, 119.35 kg of migration fluid was injected into the migration-deficient section at an injection pressure of 0.30 MPa and an injection flow rate of 24.00 kg / min. A total of 477.40 kg of migration fluid was injected into the four injection zones to replenish the slurry.
[0073] After the migration fluid replenishment slurry was injected, a biaxial mixing head was used to locally re-mix the migration deficit section of the A2 unit construction unit. During the local in-situ re-mixing, the biaxial mixing head rotated at 85 r / min, the mixing depth ranged from 1.50 to 1.70 m, and each mixing zone was reciprocated twice within the specified depth range, with each reciprocating mixing time being 3 min.
[0074] After completing the local in-situ remixing, a biaxial mixing head was used for continuous in-situ remixing. The mixing head first entered a depth of 1.70m and stirred upwards from the migration deficit section to the migration enrichment section at a speed of 80r / min and an upward speed of 0.30m / min until it reached a depth of 0.30m. Then, it stirred downwards from a depth of 0.30m to a depth of 1.70m once at a speed of 80r / min and a downward speed of 0.35m / min. Finally, it rose from a depth of 1.70m to the surface at a speed of 80r / min and an upward speed of 0.40m / min, completing the dispersion and remixing of the migration fluid replenishment slurry within the treatment depth range of the A2 unit construction unit.
[0075] The cumulative time from the completion of initial mixing to the completion of in-situ remixing in unit A2 was 198 minutes, which is 318 minutes shorter than the on-site initial setting time.
[0076] S7. Detection of differences in excitation components after compensation and determination of stopping compensation. Ten minutes after the in-situ re-stirring of the A2 unit construction unit, 500.00 g of compensated wet samples were obtained from the migration enrichment section and the migration deficit section, respectively. Following the same filtration pressure, filtration time, membrane pore size, and detection conditions as in step S3, the sodium ion concentration and soluble silica concentration in the compensated liquid phase samples were measured. The increased sodium ion concentration and increased soluble silica concentration after compensation were calculated based on the background concentration at the corresponding sampling locations before construction.
[0077] The test results before and after compensation are shown in Table 7.
[0078] Table 7. Changes in the depth of excitation components before and after compensation in unit A2 construction unit. Before compensation, the difference in the increase of sodium ions between the migration enrichment section and the migration deficit section was 156.0 mg / L, and the difference in the increase of soluble silicon was 43.0 mg / L.
[0079] After compensation, the difference in sodium ion increment between the migration enrichment segment and the migration deficit segment was 36.0 mg / L, and the difference in soluble silicon increment was 10.0 mg / L.
[0080] Therefore, the difference in sodium ion increment after compensation is reduced by 76.9% compared to before compensation, and the difference in soluble silica increment after compensation is reduced by 76.7% compared to before compensation. These reduction rates are greater than 35% and 30% respectively, meeting the conditions for ceasing further injection of migration fluid replenishment slurry. Therefore, in this embodiment, no additional replenishment reaction dry material or migration fluid replenishment slurry will be added to the A2 unit construction unit.
[0081] S8, Leveling, Compacting, and Moisturizing Maintenance After completing the in-situ mixing treatment of the three construction units A1, A2 and A3, the treated surface is leveled with a grader before initial setting on site, and the height difference of the leveled surface is controlled to not exceed 10mm.
[0082] After leveling, a single-drum vibratory roller with a working mass of 10t was used for compaction. During the compaction process, two passes of static compaction were first performed, followed by four passes of low-amplitude vibratory compaction. The roller travel speed was 2.0 km / h, and the overlap width between adjacent compaction strips was 300 mm.
[0083] After compaction, immediately cover the treated surface with a 0.10mm thick polyethylene film, and then cover the polyethylene film with a 300g / m² non-woven geotextile. During the curing period, spray water evenly onto the surface of the non-woven geotextile once each at 9:00 AM and 4:00 PM, with a water volume of 2.0kg / m² each time, for a moisturizing curing period of 7 days. After completing the 7-day moisturizing curing, continue natural curing for 28 days to form a modified foundation with a lithified matrix bearing layer.
[0084] Cylindrical specimens with a diameter of 50 mm and a height of 100 mm were drilled in the migration enrichment section, intermediate depth section and migration deficit section of the A2 unit construction unit, respectively, and the unconfined compressive strength at 7 days and 28 days was tested. The results are shown in Table 8.
[0085] Table 8. Strength results of solidified soil in construction unit A2 The unconfined compressive strength range of the three depth sections in the A2 unit construction unit at 28 days was 0.07 MPa, and the coefficient of variation of strength in the depth direction was 1.04%.
[0086] In this embodiment, sodium carbonate and anhydrous sodium metasilicate in the basic reactive dry materials first activate the cementitious reaction of granulated blast furnace slag powder, fly ash, and silicate cement clinker. Given the presence of moisture migration channels in the in-situ soil, the exudate after initial mixing carries some sodium ions and soluble silicon upwards, increasing the concentration of the activating components in the migration enrichment section and decreasing the concentration of the activating components in the migration deficit section.
[0087] In this embodiment, no liquid-absorbing powder is added to the migration enrichment section, nor is any new alkaline active activator added to the migration deficit section. Instead, the oozing liquid already carrying migration activating components is collected and used as the sole mixing liquid to form a migration liquid replenishment slurry with ultrafine blast furnace slag powder, metakaolin, and anhydrous calcium sulfate. After this replenishment slurry is injected into the migration deficit section, the sodium ions and soluble silicon in the oozing liquid can participate in the subsequent solidification reaction within the deficit section, while the ultrafine blast furnace slag powder and metakaolin provide new reaction solid phases.
[0088] Therefore, the excitation components that have migrated upward in the migration enrichment section are redirected to the migration deficit section for use. Without increasing the amount of soluble alkali salt added, the difference in excitation components in the depth direction of the treatment layer is reduced, which is expected to reduce the difference in the degree of curing reaction between the migration enrichment section and the migration deficit section, as well as the dispersion of the later bearing strength.
[0089] Comparative Example 1 This comparative example discloses a method for modifying the foundation of a rock-based bearing layer. The only difference from Example 1 is that after the existence of migration enrichment and migration deficit sections is determined by testing in the A2 unit construction unit, the effluent from the initial mixing of the soil and slurry in the A2 unit construction unit is not collected, migration fluid replenishment slurry is not prepared, migration fluid replenishment slurry is not injected into the migration deficit section, local in-situ re-mixing is not performed in the migration deficit section, and in-situ re-mixing from the migration deficit section to the migration enrichment section is not performed. Apart from the above differences, the composition and dosage of the foundation reactive dry material, the water-cement ratio of the foundation solidification slurry, the size of the unit construction unit, the in-situ soil conditions, the preparation method of the foundation solidification slurry, the in-situ initial mixing treatment method, the sampling location, the liquid phase sample preparation method, the detection method of sodium ion concentration and soluble silica concentration, and the leveling, compaction and moisturizing curing methods of this comparative example are all the same as those of Example 1.
[0090] Specifically, this comparative example still sets up three construction units: A1, A2, and A3. Each construction unit has a length of 4.00m, a width of 4.00m, an area of 16.00m², a treatment depth H of 2.00m, and an in-situ dry soil mass of 40,000.00kg within each construction unit.
[0091] Each construction unit receives 4400.00 kg of basic reactive dry material, which consists of 2244.00 kg of granulated blast furnace slag powder, 968.00 kg of silicate cement clinker, 660.00 kg of Grade I low-calcium fly ash, 308.00 kg of anhydrous gypsum, 125.84 kg of sodium carbonate, and 94.16 kg of anhydrous sodium metasilicate. The specific surface area of the granulated blast furnace slag powder is 438 m² / kg, and the specific surface area of the ground silicate cement clinker is 364 m² / kg. Each construction unit also receives 2200.00 kg of grouting water, resulting in a water-cement ratio of 0.50 for the basic curing grout.
[0092] According to the method disclosed in Example 1, the three construction units A1, A2 and A3 were subjected to foundation solidification grout injection and in-situ initial mixing treatment. At the stage where the initially mixed grout-soil mixture showed bleeding but had not yet reached the initial setting stage, the sodium ion increment and soluble silicon increment of liquid phase samples at different treatment depths were detected.
[0093] Testing revealed that the on-site sodium ion increment at the first sampling location (0.30–0.50 m continuous depth) in construction unit A2 was 576.0 mg / L, and the on-site soluble silica increment was 148.0 mg / L. At the third sampling location (1.50–1.70 m continuous depth), the on-site sodium ion increment was 420.0 mg / L, and the on-site soluble silica increment was 105.0 mg / L. Using the baseline sodium ion increment of 480.0 mg / L and the baseline soluble silica increment of 120.0 mg / L measured in Example 1 as comparison benchmarks, the first sampling location in construction unit A2 showed both sodium ion and soluble silica increments exceeding the baseline increments, while the third sampling location showed both sodium ion and soluble silica increments falling below the baseline increments.
[0094] Therefore, the 0.30–0.50 m continuous depth section corresponding to the first sampling position of the A2 unit construction unit was identified as the migration enrichment section, and the 1.50–1.70 m continuous depth section corresponding to the third sampling position was identified as the migration deficit section.
[0095] Unlike Example 1, this comparative example does not perform migration fluid replenishment after determining the migration enrichment and migration deficit sections. Specifically, it does not use a collection tank to collect the oozing fluid precipitated from the surface of the A2 unit construction unit, does not mix the oozing fluid with ultrafine blast furnace slag powder, metakaolin, and anhydrous gypsum to form a migration fluid replenishment slurry, does not inject any replenishment slurry into the continuous depth section of 1.50–1.70 m, does not perform local in-situ re-stirring in the migration deficit section, and does not implement through-situ re-stirring from the migration deficit section to the migration enrichment section.
[0096] To record the differential changes of the excitation components along the treatment depth direction without migration fluid replenishment, tracking wet samples were obtained from the migration enrichment section and the migration deficit section at the time point corresponding to the compensation detection after migration fluid replenishment and in-situ re-stirring in Example 1, i.e., 208 minutes after the initial stirring of the A2 unit construction unit. The sodium ion concentration and soluble silica concentration in the tracking liquid phase sample were determined according to the pressure filtration and detection conditions disclosed in Example 1, and the tracking sodium ion increment and tracking soluble silica increment were calculated.
[0097] The differences in the activating components before and after the migration fluid replenishment treatment in the A2 unit construction unit are shown in Table 9.
[0098] Table 9 Results of the variation in the depth of the activating component in the construction unit A2 of Comparative Example 1 According to Table 9, during the initial stirring test, the difference in sodium ion increment between the migration enrichment section and the migration deficit section was 156.0 mg / L, and the difference in soluble silicon increment was 43.0 mg / L; during the follow-up test, the difference in sodium ion increment between the migration enrichment section and the migration deficit section was 173.0 mg / L, and the difference in soluble silicon increment was 50.0 mg / L.
[0099] Therefore, without implementing migration fluid replenishment treatment, the differences in the depth of migration of the activating components that have already occurred in the A2 unit construction unit have not been reduced, with the difference in sodium ion increment increasing by 10.9% and the difference in soluble silicon increment increasing by 16.3%.
[0100] After completing the above tracking and testing, the three construction units A1, A2 and A3 were treated according to the leveling, compaction and moisturizing curing methods disclosed in Example 1. After curing for 28 days, the modified lithified bearing layer foundation without migration fluid replenishment treatment was obtained.
[0101] After curing for 7 days and 28 days, cylindrical specimens with a diameter of 50 mm and a height of 100 mm were drilled from the migration enrichment section, intermediate depth section and migration deficit section of the A2 unit construction unit, respectively. The results of unconfined compressive strength are shown in Table 10.
[0102] Table 10 Unconfined compressive strength results of construction unit A2 in Comparative Example 1 According to the data shown in Table 10, the 28-day unconfined compressive strength range of the three depth sections of the A2 unit construction unit is 0.70 MPa, and the coefficient of variation of strength in the depth direction is 10.98%.
[0103] In this comparative example, the initial mixing of the base curing slurry caused the A2 unit construction unit to exhibit an enrichment of sodium ions and soluble silica in the upper part and a deficiency of sodium ions and soluble silica in the lower part. Because the effluent from the migration-enriched section was not recovered, and the liquid phase containing migration-activating components was not reintroduced into the migration-deficient section, the degree of gelation reaction in the upper region is expected to remain higher than in the lower region. The lower region, due to insufficient activation components, will exhibit relatively lower curing strength.
[0104] Compared with Example 1, the average 28-day unconfined compressive strength of this comparative example did not decrease significantly, but the strength range and coefficient of variation along the treatment depth direction increased significantly. This result indicates that the main function of the migration fluid replenishment treatment in this scheme is not simply to increase the average strength, but rather to reduce the difference in the distribution of activating components between the migration-enriched and migration-depleted sections without the addition of additional alkaline active activators, thereby improving the bearing uniformity of the modified lithified basement in the treatment depth direction.
[0105] Comparative Example 2 This comparative example discloses a method for modifying the foundation of a lithified basement bearing layer. The only difference from Example 1 is that, after the existence of a migration enrichment section and a migration deficit section is determined by testing in the A2 unit construction unit, the migration fluid replenishment slurry prepared using the effluent from the A2 unit construction unit is injected into the migration enrichment section instead of the migration deficit section, and local in-situ re-stirring is performed in the migration enrichment section. Apart from the above differences, the composition and dosage of the basic reactive dry material, the water-cement ratio of the basic solidification slurry, the size of the unit construction unit, the in-situ soil conditions, the preparation method of the basic solidification slurry, the in-situ initial stirring treatment method, the sampling location, the liquid phase sample preparation method, the sodium ion concentration and soluble silica concentration detection method, the effluent collection method, the composition and dosage of the replenishment reactive dry material, the preparation method of the migration fluid replenishment slurry, the penetrating in-situ re-stirring method, and the leveling, compaction and moisturizing curing methods are all the same as in Example 1.
[0106] Specifically, the three construction units A1, A2 and A3 were subjected to foundation solidification grout injection and in-situ initial mixing treatment according to the method disclosed in Example 1. At the stage where the initially mixed grout-soil mixture showed bleeding but had not yet reached initial setting, the sodium ion increment and soluble silicon increment of liquid phase samples at different treatment depths of each construction unit were detected.
[0107] Testing revealed that the increase in sodium ions at the first sampling location (0.30–0.50 m depth) in construction unit A2 was 576.0 mg / L, and the increase in soluble silica was 148.0 mg / L. At the third sampling location (1.50–1.70 m depth), the increase in sodium ions was 420.0 mg / L, and the increase in soluble silica was 105.0 mg / L. Using the baseline sodium ion increase of 480.0 mg / L and the baseline soluble silica increase of 120.0 mg / L as benchmarks, the 0.30–0.50 m depth range corresponding to the first sampling location in construction unit A2 was designated as the migration enrichment range, and the 1.50–1.70 m depth range corresponding to the third sampling location was designated as the migration deficit range.
[0108] At 112 minutes after the initial mixing of the A2 unit construction unit, the oozing liquid precipitated from the surface of the initially mixed slurry-soil mixture in the A2 unit construction unit was collected according to the method disclosed in Example 1. 169.40 kg of the filtered oozing liquid was weighed and used as the sole liquid for mixing with 308.00 kg of replenishment reaction dry material to obtain 477.40 kg of migration liquid replenishment slurry.
[0109] The replenishment reaction dry material consists of 206.36 kg of ultrafine blast furnace slag powder, 77.00 kg of metakaolin, and 24.64 kg of anhydrous gypsum. The ultrafine blast furnace slag powder has a specific surface area of 617 m² / kg, and the metakaolin has a particle size D50 of 4.0 μm. No sodium carbonate, anhydrous sodium metasilicate, sodium hydroxide, or potassium hydroxide are added to the replenishment reaction dry material.
[0110] Unlike Example 1, which injects the migration fluid replenishment slurry into the migration deficit section, this comparative example injects the migration fluid replenishment slurry into the migration enrichment section of the A2 unit construction unit, that is, a continuous depth section 0.30 to 0.50 m from the original foundation surface.
[0111] The A2 unit construction unit is divided into two equal parts along both the length and width directions to form four injection zones with dimensions of 2.00m × 2.00m. 119.35kg of migration fluid and backfill grout is injected into each injection zone.
[0112] A hollow grouting mixing rod with lateral grout outlets was used for directional injection. The outer diameter of the hollow grouting mixing rod was 60 mm, and the lateral grout outlets were located at positions 100 mm, 150 mm, and 200 mm from the end of the rod. During construction, the hollow grouting mixing rod was inserted to a depth of 0.45 m from the original foundation surface, so that the lateral grout outlets were located within the migration enrichment section within a range of 0.30–0.50 m. In each injection zone, 119.35 kg of migration fluid was injected into the migration enrichment section at an injection pressure of 0.30 MPa and an injection flow rate of 24.00 kg / min. A total of 477.40 kg of migration fluid was injected into the four injection zones as replenishment grout.
[0113] After the migration fluid replenishment slurry injection was completed, a biaxial mixing head was used to perform local in-situ re-mixing of the migration enrichment section of the A2 unit construction unit. During local in-situ re-mixing, the rotation speed of the biaxial mixing head was 85 r / min, the mixing depth range was 0.30-0.50 m, and each mixing zone was reciprocated twice within the specified depth range, with each reciprocating mixing time being 3 min.
[0114] After completing the local in-situ re-mixing of the migration enrichment section, the process was carried out according to the through-through in-situ re-mixing method disclosed in Example 1. The dual-shaft mixing head first entered a depth of 1.70m and stirred upwards from a depth of 1.70m to a depth of 0.30m at a rotation speed of 80r / min and an upward speed of 0.30m / min; then it stirred downwards from a depth of 0.30m to a depth of 1.70m once at a rotation speed of 80r / min and a downward speed of 0.35m / min; finally, it rose from a depth of 1.70m to the surface at a rotation speed of 80r / min and an upward speed of 0.40m / min, completing the through-through in-situ re-mixing.
[0115] The cumulative time from the completion of initial mixing to the completion of in-situ remixing in unit A2 was 198 minutes, which is 318 minutes shorter than the on-site initial setting time.
[0116] Ten minutes after the completion of in-situ re-stirring in Unit A2, compensated wet samples were obtained from the migration enrichment section and the migration deficit section, respectively. Following the pressure filtration and detection conditions disclosed in Example 1, the sodium ion concentration and soluble silicon concentration in the compensated liquid phase samples were determined, and the increases in sodium ions and soluble silicon after compensation were calculated.
[0117] The results of the difference in the depth of the excitation component before and after compensation of the A2 unit construction unit are shown in Table 11.
[0118] Table 11 Results of the changes in the depth of the activating component before and after compensation in the A2 unit construction unit of Comparative Example 2 Before compensation, the difference in the increase of sodium ions between the migration enrichment section and the migration deficit section was 156.0 mg / L, and the difference in the increase of soluble silicon was 43.0 mg / L.
[0119] After compensation, the difference in sodium ion increment between the migration enrichment segment and the migration deficit segment was 119.0 mg / L, and the difference in soluble silicon increment was 32.0 mg / L.
[0120] Based on this calculation, the difference in sodium ion increment after compensation is reduced by 23.7% compared to before compensation, and the difference in soluble silicon increment after compensation is reduced by 25.6% compared to before compensation. These reduction percentages are both lower than the conditions set in Example 1 for stopping compensation when the difference in sodium ion increment is reduced by no less than 35% and the difference in soluble silicon increment is reduced by no less than 30%.
[0121] After completing the above tests, the three construction units A1, A2 and A3 were treated according to the leveling, compaction and moisturizing curing methods disclosed in Example 1. After curing for 28 days, the modified foundation of the lithified base bearing layer of this comparative example was obtained.
[0122] After curing for 7 days and 28 days, cylindrical specimens with a diameter of 50 mm and a height of 100 mm were drilled from the migration enrichment section, intermediate depth section and migration deficit section of the A2 unit construction unit, respectively. The results of unconfined compressive strength are shown in Table 12.
[0123] Table 12 Unconfined compressive strength results of construction unit A2 in Comparative Example 2 According to the data shown in Table 2, the 28-day unconfined compressive strength range of the three depth sections of the A2 unit construction unit is 0.62 MPa, and the coefficient of variation of strength in the depth direction is 9.13%.
[0124] In this comparative example, although the effluent from the construction unit A2 was also collected, and a migration fluid replenishment slurry without added alkaline active activator was prepared using this effluent, the replenishment slurry was injected into the migration enrichment section, which was already enriched in sodium ions and soluble silica. Therefore, the liquid-phase activating components and reactive solid phases in the replenishment slurry preferentially concentrated in the upper region, allowing the migration enrichment section to obtain more sufficient gelation reaction conditions, while the migration deficit section could only obtain limited indirect dispersion compensation through subsequent in-situ re-stirring.
[0125] Therefore, compared to the method in Example 1 where the migration fluid replenishment slurry was directly injected into the migration-deficient section, although this comparative example could reduce the difference in the depth of the activating components through in-situ re-stirring, the reduction was insufficient, and the 28-day unconfined compressive strength still showed significant depth dispersion. This result demonstrates that simply collecting the bleeding fluid and preparing the replenishment slurry is insufficient to achieve homogenization of the load-bearing layer; directional injection of the migration fluid replenishment slurry into the migration-deficient section is a key step in reducing the difference in the depth of the activating components and improving the uniformity of load bearing.
[0126] Comparative Example 3 This comparative example discloses a method for modifying the foundation of a lithified basement bearing layer. The only difference from Example 1 is that after the existence of migration enrichment and migration deficit sections in the A2 unit construction unit is determined by testing, the migration fluid replenishment slurry prepared using the bleed fluid precipitated from the A2 unit construction unit is injected uniformly in layers along the treatment depth range of the A2 unit construction unit, instead of injecting the migration fluid replenishment slurry directionally into the migration deficit section; after completing the uniform layer injection, the A2 unit construction unit is homogenized and re-stirred at the full treatment depth, instead of first performing local in-situ re-stirring in the migration deficit section. Except for the differences mentioned above, the composition and dosage of the basic reactive dry material, the water-cement ratio of the basic curing slurry, the unit construction unit size, the in-situ soil conditions, the preparation method of the basic curing slurry, the in-situ initial mixing treatment method, the sampling location, the liquid phase sample preparation method, the sodium ion concentration and soluble silicon concentration detection method, the bleeding fluid collection method, the composition and dosage of the replenishing reactive dry material, the preparation method of the migration fluid replenishing slurry, and the leveling, compaction and moisturizing curing methods are all the same as those in Example 1.
[0127] Specifically, the three construction units A1, A2 and A3 were subjected to foundation solidification grout injection and in-situ initial mixing treatment according to the method disclosed in Example 1. At the stage where the initially mixed grout-soil mixture showed bleeding but had not yet reached initial setting, the sodium ion increment and soluble silicon increment of liquid phase samples at different treatment depths of each construction unit were detected.
[0128] Testing revealed that the increase in sodium ions at the first sampling location (0.30–0.50 m depth) in construction unit A2 was 576.0 mg / L, and the increase in soluble silica was 148.0 mg / L. At the third sampling location (1.50–1.70 m depth), the increase in sodium ions was 420.0 mg / L, and the increase in soluble silica was 105.0 mg / L. Using the baseline sodium ion increase of 480.0 mg / L and the baseline soluble silica increase of 120.0 mg / L as benchmarks, the 0.30–0.50 m depth range at the first sampling location in construction unit A2 was designated as the migration enrichment range, and the 1.50–1.70 m depth range at the third sampling location was designated as the migration deficit range.
[0129] At 112 minutes after the initial mixing of the A2 unit construction unit, the oozing liquid precipitated from the surface of the initially mixed slurry-soil mixture in the A2 unit construction unit was collected according to the method disclosed in Example 1. 169.40 kg of the filtered oozing liquid was weighed and used as the sole liquid for mixing with 308.00 kg of replenishment reaction dry material to obtain 477.40 kg of migration liquid replenishment slurry.
[0130] The replenishment reaction dry material consists of 206.36 kg of ultrafine blast furnace slag powder, 77.00 kg of metakaolin, and 24.64 kg of anhydrous gypsum. The ultrafine blast furnace slag powder has a specific surface area of 617 m² / kg, and the metakaolin has a particle size D50 of 4.0 μm. No sodium carbonate, anhydrous sodium metasilicate, sodium hydroxide, or potassium hydroxide are added to the replenishment reaction dry material.
[0131] Unlike Example 1, where all the migration fluid replenishment slurry was injected directionally into the migration deficit section, this comparative example injects the migration fluid replenishment slurry in layers along the treatment depth range of the A2 unit construction unit.
[0132] The A2 unit construction cell is divided into two equal parts along both its length and width, forming four injection zones each measuring 2.00m × 2.00m. Within each injection zone, four injection depths are set at center depths of 0.40m, 0.80m, 1.20m, and 1.60m, respectively. The injection depth at center depth of 0.40m is located within the migration enrichment zone, and the injection depth at center depth of 1.60m is located within the migration deficit zone.
[0133] 477.40 kg of migration fluid replenishment slurry was evenly distributed to four injection depth positions, with a total mass of 119.35 kg of migration fluid replenishment slurry corresponding to each injection depth position. The migration fluid replenishment slurry corresponding to each injection depth position was then evenly distributed to four injection zones, with each injection zone injecting 29.8375 kg of migration fluid replenishment slurry at each injection depth position.
[0134] The same hollow grouting mixing rod with lateral grout outlets as in Example 1 was used for injection. During construction, the insertion depth of the hollow grouting mixing rod was adjusted sequentially so that the lateral grout outlets corresponded to injection depths of 0.40m, 0.80m, 1.20m, and 1.60m from the center depth, respectively. At each injection depth, the injection pressure was controlled at 0.30MPa, and the injection flow rate was controlled at 12.00kg / min, uniformly injecting the migration fluid replenishment grout within the corresponding depth range.
[0135] After the migration fluid replenishment slurry is injected in layers and uniformly, this comparative example does not perform local in-situ re-mixing in the migration loss section, but directly uses a dual-shaft mixing head to perform full-depth homogenization and re-mixing of the A2 unit construction unit.
[0136] During the full-depth homogenization and re-mixing process, the biaxial mixing head enters from the ground surface to a treatment depth of 2.00m, controlling the rotation speed of the biaxial mixing head at 80 r / min and the downward speed at 0.35 m / min. After reaching the 2.00m treatment depth, it moves back to the ground surface at a rotation speed of 80 r / min and an upward speed of 0.35 m / min. Subsequently, it completes one downward re-mixing and one upward re-mixing at the same rotation speed and speed. By adjusting the re-mixing stroke interval, the cumulative treatment time from the injection of the migration fluid replenishment slurry to the completion of re-mixing in this comparative example is consistent with the cumulative treatment time from the injection of the migration fluid replenishment slurry to the completion of in-situ re-mixing in Example 1.
[0137] The cumulative time from the completion of initial mixing to the end of homogenization and remixing at the full treatment depth for unit A2 is 198 minutes, which is 318 minutes shorter than the on-site initial setting time.
[0138] Ten minutes after the completion of homogenization and re-stirring at the full treatment depth in the A2 unit construction unit, compensated wet samples were obtained from the migration enrichment section and the migration deficit section, respectively. Following the pressure filtration and detection conditions disclosed in Example 1, the sodium ion concentration and soluble silica concentration in the compensated liquid phase sample were measured. Based on the background sodium ion concentration and background soluble silica concentration measured before construction at the corresponding sampling locations, the increases in sodium ion concentration and soluble silica concentration after compensation were calculated.
[0139] The results of the difference in the depth of the excitation component before and after compensation of the A2 unit construction unit are shown in Table 13.
[0140] Table 13 Results of changes in the depth of the activating component before and after compensation in the A2 unit of construction in Comparative Example 3 Before compensation, the difference in the increase of sodium ions between the migration enrichment section and the migration deficit section was 156.0 mg / L, and the difference in the increase of soluble silicon was 43.0 mg / L.
[0141] After compensation, the difference in sodium ion increment between the migration enrichment segment and the migration deficit segment was 77.0 mg / L, and the difference in soluble silicon increment was 24.0 mg / L.
[0142] Based on these calculations, the difference in sodium ion increment after compensation decreased by 50.6% compared to before compensation, and the difference in soluble silicon increment after compensation decreased by 44.2% compared to before compensation. Although the method of uniform injection in layers at the full treatment depth can reduce the difference in excitation components between the migration enrichment section and the migration deficit section, the degree of reduction is significantly lower than the detection results after the migration liquid replenishment slurry was directionally injected into the migration deficit section in Example 1.
[0143] After completing the above tests, the three construction units A1, A2 and A3 were treated according to the leveling, compaction and moisturizing curing methods disclosed in Example 1. After curing for 28 days, the modified foundation of the lithified base bearing layer of this comparative example was obtained.
[0144] After curing for 7 days and 28 days, cylindrical specimens with a diameter of 50 mm and a height of 100 mm were drilled from the migration enrichment section, intermediate depth section and migration deficit section of the A2 unit construction unit, respectively. The results of unconfined compressive strength are shown in Table 14.
[0145] Table 14 Unconfined compressive strength results of construction unit A2 in Comparative Example 3 According to the data shown in Table 14, the 28-day unconfined compressive strength range of the three depth sections of the A2 unit construction unit is 0.33 MPa, and the coefficient of variation of strength in the depth direction is 5.02%.
[0146] In this comparative example, although the effluent from the construction unit A2 was also recovered, and the effluent was used as the sole liquid for preparing a migration fluid replenishment slurry without added alkaline active activator, the migration fluid replenishment slurry was injected evenly in layers along the treatment depth range. Part of the migration fluid replenishment slurry re-entered the upper region, which was already enriched with sodium ions and soluble silica, and part entered the middle depth region, which did not show obvious depletion of activating components. Only a portion of the migration fluid replenishment slurry entered the migration-depleted section.
[0147] Therefore, compared to Example 1, where the replenishment slurry was concentrated and injected into the migration deficit section, the effective replenishment amount used to compensate for the deficit of the lower activating components in this comparative example is reduced. Although full-depth homogenization and re-stirring can promote the redispersibility of the replenishment slurry between different depth regions, significantly reducing the difference in activating components compared to Comparative Example 1 without replenishment treatment, it cannot fully utilize the directional compensation effect of the enriched oozing liquid on the migration deficit section.
[0148] Compared to Example 1, the 28-day average unconfined compressive strength of this comparative example is expected to be similar, but the strength range and coefficient of variation in the depth direction are significantly increased. This result demonstrates that, after confirming the existence of migration-enriched and migration-deficient sections, simply adding the migration fluid replenishment slurry uniformly along the entire treatment depth cannot achieve the same homogenization effect as directional injection into the migration-deficient section. Concentrated introduction of the replenishment slurry into the migration-deficient section is a key technical measure to reduce the depth difference of the activating components and improve the bearing uniformity of the lithified matrix bearing stratum.
[0149] The above description is merely a preferred embodiment of the present invention. The scope of protection of the present invention is not limited to the above embodiments. All technical solutions falling within the scope of the present invention's concept are within the scope of protection of the present invention. It should be noted that for those skilled in the art, any improvements and modifications made without departing from the principles of the present invention should also be considered within the scope of protection of the present invention.
Claims
1. A method for treating foundations modified from lithified basement bearing strata, characterized in that, Includes the following steps: S1: Divide the in-situ foundation to be treated into multiple unit construction units, each unit construction unit having the same area and treatment depth, denoted as H; set no less than three sampling positions along the treatment depth direction within each unit construction unit, and obtain soil samples before construction from each sampling position, prepare soil sample leachates under the same leachate conditions, and determine the background sodium ion concentration and background soluble silica concentration in each soil sample leachate; mix and homogenize each of the soil samples before construction according to the same dry soil mass fraction to obtain a reference soil sample, and determine the reference background sodium ion concentration and reference background soluble silica concentration in the reference soil sample leachate; S2: Mix the basic reactive dry material with water according to the water-cement ratio to obtain the basic curing slurry; mix the basic curing slurry with the reference soil sample according to the same dry soil content of the basic reactive dry material to obtain the reference initial mixed body; and inject the basic curing slurry into the in-situ soil of each of the above-mentioned construction units for in-situ mixing to obtain the on-site initial mixed slurry-soil mixture of each of the above-mentioned construction units. S3: When the initial mixing of the soil and slurry on site shows bleeding but has not yet reached the initial setting stage, a reference wet sample is obtained from the reference initial mixing mixture, and on-site wet samples are obtained from each of the sampling locations of each of the unit construction units. Under the same pressure filtration conditions, solid-liquid separation was performed on the reference wet sample and each of the field wet samples to obtain the reference liquid phase sample and the field liquid phase sample corresponding to each of the sampling locations. The sodium ion concentration and soluble silicon concentration in the reference liquid phase sample and each of the field liquid phase samples were determined respectively; S4: The difference between the sodium ion concentration in the reference liquid sample and the reference background sodium ion concentration is determined as the reference sodium ion increment, and the difference between the soluble silicon concentration in the reference liquid sample and the reference background soluble silicon concentration is determined as the reference soluble silicon increment. The difference between the sodium ion concentration in each of the in-situ liquid phase samples and the background sodium ion concentration at the corresponding sampling location is determined as the in-situ sodium ion increment, and the difference between the soluble silicon concentration in each of the in-situ liquid phase samples and the background soluble silicon concentration at the corresponding sampling location is determined as the in-situ soluble silicon increment. When the in-situ sodium ion increment and in-situ soluble silica increment corresponding to at least one sampling position located above the treatment depth in a unit construction unit are both higher than the corresponding reference sodium ion increment and reference soluble silica increment, and the in-situ sodium ion increment and in-situ soluble silica increment corresponding to at least one sampling position located below the sampling position are both lower than the corresponding reference sodium ion increment and reference soluble silica increment, the unit construction unit is determined as a migration replenishment construction unit; the continuous depth segment where the in-situ sodium ion increment and in-situ soluble silica increment are both higher than the corresponding reference increment is determined as a migration enrichment segment, and the continuous depth segment located below the migration enrichment segment where the in-situ sodium ion increment and in-situ soluble silica increment are both lower than the corresponding reference increment is determined as a migration deficit segment; S5: Collect the oozing liquid that precipitates from the initial mixed slurry before it reaches initial setting in the migration and replenishment construction unit. Use the oozing liquid as the only mixing liquid and mix it with the replenishment reaction dry material to obtain the migration liquid replenishment slurry. The replenishment reaction dry material does not contain sodium carbonate, sodium metasilicate, sodium hydroxide, or potassium hydroxide. S6: Inject the migration fluid replenishment slurry into the migration deficit section, and perform local in-situ re-stirring in the migration deficit section. Then, perform penetrating in-situ re-stirring along the direction from the migration deficit section to the migration enrichment section, so that the migration fluid replenishment slurry is dispersed within the treatment depth range of the migration replenishment construction unit. S7: After completing the in-situ re-stirring and before the initial setting of the on-site mixed slurry, take compensated wet samples from the migration enrichment section and the migration deficit section respectively, and measure the compensated sodium ion increment and compensated soluble silicon increment under the same pressure filtration conditions and detection conditions as in step S3. When the difference in sodium ion increment after compensation between the migration enrichment section and the migration deficit section is less than the difference in sodium ion increment before re-stirring, and the difference in soluble silica increment after compensation is less than the difference in soluble silica increment before re-stirring, the injection of migration liquid to replenish the slurry in the migration deficit section is stopped. S8: Level, compact and moisturize the in-situ foundation after in-situ mixing treatment to form a modified foundation with lithified matrix bearing layer; The basic reaction dry materials include granulated blast furnace slag powder, silicate clinker, fly ash, anhydrous gypsum and alkaline active activator, wherein the alkaline active activator includes sodium carbonate and anhydrous sodium metasilicate. The water-cement ratio is the ratio of the mass of water in the base curing slurry to the mass of the base reactive dry material.
2. The method for modifying the foundation of the lithified basement bearing layer according to claim 1, characterized in that, In step S1, three sampling positions are set along the treatment depth direction within each unit construction unit. The three sampling positions are located at depths of 0.15H to 0.25H, 0.45H to 0.55H, and 0.75H to 0.85H from the surface of the original foundation, respectively. The soil sample before construction is formed by mixing soil samples obtained from at least two sampling points circumferentially distributed at the corresponding sampling positions.
3. The method for modifying the foundation of the lithified basement bearing layer according to claim 1, characterized in that, The same extraction conditions in step S1 include the same dry soil mass, the same water-to-soil mass ratio, the same shaking time, the same settling time, the same solid-liquid separation method, and the same detection temperature. The same pressure filtration conditions in step S3 include the same wet sample volume, the same pressure filtration pressure, the same pressure filtration time, and the same filter membrane pore size; The sodium ion concentration was determined by inductively coupled plasma atomic emission spectrometry, and the soluble silicon concentration was determined by molybdenum blue spectrophotometry.
4. The method for modifying the foundation of the lithified basement bearing layer according to claim 1, characterized in that, Based on a total mass of 100 parts by mass of the basic reaction dry material, the basic reaction dry material consists of 48-54 parts by mass of granulated blast furnace slag powder, 20-24 parts by mass of silicate clinker, 14-18 parts by mass of fly ash, 7-9 parts by mass of anhydrous gypsum, and 5-7 parts by mass of alkaline active activator.
5. The method for modifying the foundation of the lithified basement bearing layer according to claim 4, characterized in that, The mass ratio of sodium carbonate to anhydrous sodium metasilicate in the alkaline active activator is 1:0.65-0.80; the mass of the basic reaction dry material accounts for 9%-13% of the mass of the dry soil in situ within the corresponding construction unit; and the water-cement ratio is 0.43-0.
58.
6. The method for modifying the foundation of the lithified matrix bearing layer according to claim 1, characterized in that, The replenishment reaction dry material includes granulated blast furnace slag powder, metakaolin, and anhydrous gypsum; based on a total mass of 100 parts by mass of the replenishment reaction dry material, the replenishment reaction dry material consists of 62-72 parts by mass of granulated blast furnace slag powder, 20-30 parts by mass of metakaolin, and 6-10 parts by mass of anhydrous gypsum.
7. The method for modifying the foundation of the lithified basement bearing layer according to claim 6, characterized in that, The specific surface area of the granulated blast furnace slag powder in the basic reactive dry material is 400-480 m². 2 / kg, the specific surface area of the granulated blast furnace slag powder in the replenished dry material is 560-680m². 2 / kg, the particle size D50 of the metakaolin is 2-6μm.
8. The method for modifying the foundation of the lithified matrix bearing layer according to claim 1, characterized in that, In step S4, when the increase in the on-site sodium ion increment in the migration enrichment section is not less than 12% relative to the reference sodium ion increment, and the increase in the on-site soluble silicon increment in the migration enrichment section is not less than 10% relative to the reference soluble silicon increment, and the decrease in the on-site sodium ion increment in the migration deficit section is not less than 8% relative to the reference sodium ion increment, and the decrease in the on-site soluble silicon increment in the migration deficit section is not less than 8% relative to the reference soluble silicon increment, the corresponding unit construction unit is determined as the migration replenishment construction unit.
9. The method for modifying the foundation of the lithified basement bearing layer according to claim 1, characterized in that, In step S5, the mass ratio of the oozing liquid to the replenishment reaction dry material is 0.45:1 to 0.70:1; the mass of the replenishment reaction dry material added to one of the migration replenishment construction units is 4% to 10% of the mass of the basic reaction dry material already added in that migration replenishment construction unit.
10. The method for modifying the foundation of the lithified matrix bearing layer according to claim 8, characterized in that, In step S7, when the difference in sodium ion increment after compensation between the migration enrichment section and the migration deficit section decreases by no less than 35% relative to the difference in sodium ion increment before re-stirring, and the difference in soluble silica increment after compensation between the migration enrichment section and the migration deficit section decreases by no less than 30% relative to the difference in soluble silica increment before re-stirring, the injection of migration liquid to replenish the slurry in the migration deficit section is stopped. When the difference in sodium ion increment or the difference in soluble silicon increment after compensation does not meet the aforementioned reduction ratio, steps S5 to S7 shall be repeated before the initial setting of the on-site mixed slurry reaches the initial setting stage; the cumulative mass of the replenished reactive dry material shall not exceed 12% of the mass of the basic reactive dry material already added in the migration replenishment construction unit.
Citation Information
Patent Citations
Technique for reinforcing organic matter soft soil by concrete and coal ash secondary stirring powder spraying method
CN101349060B
Determination method for uniformity of soil-cement admixture based on joint test of pH value and conductivity
CN102980919B
A geopolymer for treating saline soil foundation and its preparation method and application
CN105541138B